Aircraft Position Prediction during the Crosswind Approach - Marek Grzegorzewski; Jerzy Biały (Communications - Scientific letters of the University of Zilina, 2022)
Testing the impact of the drag coefficient on an F16 aircraft model, depending on the angle of attack a was performed. First, a navigation model was introduced describing the preliminary and computational assumptions of the model. The final part of the present paper contains the relationships between the wind angle and the wind correction angle at the angle of attack a = 00, a = 110, a = 130 for a full-scale F-16 aircraft. The tables present results of all the calculations for individual angles of attack, taking into account variable wind angles relative to the longitudinal axis of the runway. The values show the corrections calculated for an 1/19 scale aircraft model and for a full-scale F16 aircraft. The "right" and "left" designations represent the direction from which the wind blows in relation to the aircraft.